Aktiviti perdagangan pedagang Arab-Parsi di semenanjung Tanah Melayu berdasarkan sumber asing dan data arkeologi - Zuliskandar Ramli,; Nik Hassan Shuhaimi Nik Abd. Rahman, (Universiti Kebangsaan Malaysia, 2009)
Foreign sources especially from the Chinese and archaeological data showed that the Middle-Eastern traders pioneered by the Persian arrived in Malay Peninsula since the beginning of 3rd century AD. Some of the scholars suggested that the Middle –Eastern traders only arrived in Malay World at about 8th century AD – 9th century AD based on artifacts found in the archaeological sites situated along the Strait of Melaka. From 8th Century AD, the Arab traders were the dominant players in the Malay Peninsula and they masters their sailing skill from the Persian as we all knows that the Persian were very excellent in ship making and their sailing technique. Based on archaeological research, artifacts that usually connected with the Middle –Eastern traders were Persian ceramics or Middle-Eastern ceramics, glass product such as perfumes container or oil lamp and beads made from glass or semi precious stone. These artifacts usually found in the Bujang Valley, Kedah and Kuala Selinsing, Matang, Perak, two main archaeological sites in Malaysia. The finding showed the contributions of Arab-Persia traders in the Malays World and their existence during that practical time. Other ancient ports that also have been visited by the Arab- Persian trades are Palembang, Jambi, Lamuri (Acheh), Takuapa, Pattani and Chaiya. The product that their bought from the Malays are spices, camphor, sandalwood, forest goods, cinnamons and resin while the Arabs export product such as ceramics, glass products, iron tools, ornaments, weapon, silvers, beads, nails, silk, and perfumes